(untitled) (Journal of Partial Differential Equations, 2004)
In this paper, we prove the existence and uniqueness of global solutions in H^s(R^3) (s ∈ R, s ≥ 0) for the initial value problem of the bipolar Schrödinger-Poisson systems.